2021
DOI: 10.3390/foods10102497
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characteristics and Lipid Oxidative Stability of Zebra (Equus Burchelli) Droëwors Made Using Different Levels of Sheep Fat

Abstract: The physico-chemical properties (proximate, salt content, water activity (aw), pH) and lipid oxidation of droëwors (dried salted/spiced meat sausages) produced with zebra meat and different sheep fat levels (10, 15, and 20% by weight) measured at day 0 (before drying), day 2 (after drying at 30 °C and 40% relative humidity), and over a 90 day storage (day 17, 32, 47, 62, 77, and 92) under vacuum at 25 °C were investigated. The use of lower fat levels (10 and 15%) in the formulation resulted in higher weight lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Other similar studies have reported that droëwors made with lower fat inclusion levels resulted in lower moisture content after drying and higher protein and ash content [ 21 ]. Droëwors with higher fat inclusion levels have a higher moisture content because fat has a barrier effect on moisture transfer during drying [ 22 ]. The range of fat in chicken droëwors in this study (14.37-26.13%) was lower than the fat content of common droëwors made from beef (25.0-40.3 g/100 g), game meat (16.8-47.0 g/100 g), and ostrich (23.5-28.8 g/100 g).…”
Section: Discussionmentioning
confidence: 99%
“…Other similar studies have reported that droëwors made with lower fat inclusion levels resulted in lower moisture content after drying and higher protein and ash content [ 21 ]. Droëwors with higher fat inclusion levels have a higher moisture content because fat has a barrier effect on moisture transfer during drying [ 22 ]. The range of fat in chicken droëwors in this study (14.37-26.13%) was lower than the fat content of common droëwors made from beef (25.0-40.3 g/100 g), game meat (16.8-47.0 g/100 g), and ostrich (23.5-28.8 g/100 g).…”
Section: Discussionmentioning
confidence: 99%
“…Game meat could also be considered for meat preparation and products, in which the peculiar quality traits of the meat could be preserved [ 10 ] or even enhanced with a specific ingredient. Taking into consideration that the higher amount of polyunsaturated fatty acid in this meat could negatively affect the oxidative stability of the products, the addition of other fat sources, such as sheep fat in Zebra ( Equus burchelli ) Droëwors [ 11 ] or vegetable oils in deer burger [ 12 ], should be considered.…”
mentioning
confidence: 99%